Two new species of Nitzschia (Bacillariophyceae) from freshwater environs of Lonar Crater Lake, India. Issue 1 (23rd October 2014) - Alakananda, Batni; Karthick, Balasubramanian; Taylor, Jonathan C.; Hamilton, Paul B.
Summary Diatom taxa in India were first documented by Ehrenberg and subsequently many studies have focused on the Western Ghats and Himalayan mountains while other regional environments were rarely explored. In the current study, the freshwater environs of the saline Lonar Crater Lake were investigated and two new Nitzschia species have been described. Nitzschia kociolekii sp. nov. and Nitzschia tripudio sp. nov. were sampled from bird feeding ponds associated with Lonar Lake. The morphological characters of the new species are similar to N. amphibia and N. frustulum but differ in terms of striae pattern, polymorphic areolae development, fibula and stria density. In addition, larger specimens of N. williamsii, a recently described taxon from Bangalore wetlands of Peninsular India, were found in a waterfalls flowing into Lonar Lake. All three taxa are freshwater diatoms and are possibly endemic to Peninsular India.